Edukasi Bahan Pangan Lokal dan Literasi Kreatif untuk Mendukung UMKM Desa Sejak Dini: Penelitian - Roy Ganendo; David Marcellino; Arief Budiharjo; Mersa Nia Ramayani; Rena Febriani; Khairunnisa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service program aims to enhance elementary school students’ knowledge and awareness of the utilization of local food resources and creative communication literacy as an effort to support the strengthening of Micro, Small, and Medium Enterprises (MSMEs) from an early age. The program was implemented through the Community Service Program (Kuliah Kerja Nyata/KKN) targeting students of SDN 129 OKU in Lekis Rejo Village, Ogan Komering Ulu Regency. The methods applied included educational socialization, participatory approaches, interactive discussions, and simple practical activities introducing local food products and creative communication. The results indicate an improvement in students’ understanding of the types and benefits of local food resources, as well as their basic ability to express creative ideas related to MSME products. This program contributes to fostering awareness of local potential.